Advanced Word 2010 - Conway, Pamela; Safari eBooks ([S.l.] : CompuWorks, 2012)
"This course is designed to take you to the next level with Word 2010. The training will focus on advanced navigation techniques using the Browse Buttons and the Navigation Pane, using web components, inserting and working with graphics and images, and working with multilevel lists. You will also learn how to add references in a document, such as footnotes, endnotes, cross references and bookmarks. Time will be spent covering creating simple macros, customizing Word, sharing documents and creating a Table of Figures."--Resource description page.
Title from title screen.
Publication information from resource description page (viewed Apr. 9, 2013).
Presenter, Pamela Conway.
Keywords: Microsoft Word; Word processing; Electronic books